Hospitality management curriculum and potential market competencies - Maraouch, Fadila (2014)
Background: The recurring dilemma encountered by the academic programs in the Hospitality Management field is how applicable these programs are to the realities of the job market. That is, matching academic preparation to desired competencies sought by the market. This paper provides a positive insight into the elements that have led to the success of the curriculum of the Hospitality Management Department at the American University of Science and Technology (AUST) in Lebanon. It is a unique case which offers lessons to be learned, and which are applicable on a larger scale. Aims: This paper presents a brief description of the travel and tourism sector in Lebanon, and the requirements necessary in the development of adequate human resources to cover the market’s needs. The paper provides necessary facts to assess the potentiality of the university’s graduates and what the Faculty of Business and Economics of AUST can offer to create a value-added workforce. Study Design: This study is exploratory in nature using literature reviews and followed by a questionnaire survey which was distributed to a convenient sample of employers. Descriptive statistics was employed to offer a first-hand interpretation of the collected data. Statistical analysis using regression analysis and reliability calculations are used to study employers’ choice of competencies observed in AUST graduates. Place and Duration of Study: Sample: Lebanese hotels and restaurants, between June 2013 and October 2013. Methodology: The study used a mix of qualitative and quantitative approaches needed to build the necessary literature review, using secondary data and reported interviews with prominent hospitality employers and experts, in addition to a questionnaire survey conducted on 33 human resource managers who were willing to provide feedback on AUST’s Hospitality Management employees’ performance. Descriptive analysis was performed using SPSS-20 software. Results: The analysis of the results and findings furnished significant proof necessary to provide evidence that the current curriculum at AUST fits the job-market environment in Lebanon. Conclusion: This paper posits that continuous improvement in the Hospitality Management Curriculum is a must to keep abreast of the needs of the job market. It also offers recommendations and discloses limitations as to the definition of the mutual relationship between graduates and the hospitality employers.